The existential dimensions of the paradox of becoming in the process turn in organisation studies. Issue 4 (September 2017) - Segal, Steven
This article offers a theory of becoming a manager which goes beyond Maslow and Rogers' theory of self-actualisation. Based on two process perspectives in the context of organisations and management, it argues that becoming is less about 'inner-self' but emerges out of the dialectical interaction between a person and the world: a manager only becomes a manager as they engage with the world. Based on existential philosophers, it argues that the dialectical activity of becoming a manager through interacting with the world presupposes the willingness to leap through the anxiety of the unfamiliar and unknown so that a managerial identity and way of being can emerge. Existentialism and Organization Studies–based process theory are brought together by the way in which Karl Weick uses a quotation from Kierkegaard: 'Life is lived forward and understood backward'. This statement is also used as a basis for suggesting a way of working with the relationship between theory and practice in management.